2019
DOI: 10.1186/s12885-019-5387-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the prevalence of thrombosis and bleeding at diagnosis of Philadelphia-negative myeloproliferative neoplasms

Abstract: Background Philadelphia (Ph) chromosome-negative myeloproliferative neoplasms (MPNs) are a heterogeneous group of hematopoietic stem cell clonal diseases. Most patients with MPN are asymptomatic at diagnosis although some of them suffer from constitutional symptoms. Thrombosis and bleeding can also be one of the initial manifestations although the reported prevalence varied considerably across the studies. This systematic review and meta-analysis was conducted with the aims to better understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
115
3
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(130 citation statements)
references
References 47 publications
4
115
3
8
Order By: Relevance
“…The most recent reviews on bleeding of MPN patients present a prevalence at diagnosis and an incidence during follow-up of 7.3 and 9% in ET and 6.9 and 8% in PV, respectively. 9,57,58 Thrombotic complications remain more frequent in this population (up to 39% of patients 16 Currently, management of PV and ET patients is based on European Leukemia Network (ELN) criteria for thrombotic risk evaluation (age over 60 years and/or history of thrombosis). Interestingly, patients with platelet counts over 1,500 G/L are also considered high-risk patients, because of increased bleeding risk.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent reviews on bleeding of MPN patients present a prevalence at diagnosis and an incidence during follow-up of 7.3 and 9% in ET and 6.9 and 8% in PV, respectively. 9,57,58 Thrombotic complications remain more frequent in this population (up to 39% of patients 16 Currently, management of PV and ET patients is based on European Leukemia Network (ELN) criteria for thrombotic risk evaluation (age over 60 years and/or history of thrombosis). Interestingly, patients with platelet counts over 1,500 G/L are also considered high-risk patients, because of increased bleeding risk.…”
Section: Discussionmentioning
confidence: 99%
“…5 6 A very recent meta-analysis estimated that the overall prevalence of thrombosis in patients with myeloproliferative neoplasms (MPNs) is 20% with the prevalence of arterial thrombosis (cerebrovascular disease, transient ischemic attack, coronary artery disease, and peripheral artery disease) being 16.2% and VTE being 6.2%. 7 Another meta-analysis led to the conclusion that JAK2V617F mutation in PMF patients is associated with an increased risk of thrombosis (odds ratio: 1.76, 95% confidence interval [CI]: 0.91–3.41). 4…”
Section: Overviewmentioning
confidence: 99%
“…Thromboembolic complications are prevalent in essential thrombocythemia (ET). A recent meta‐analysis including 13 436 patients with classical MPNs revealed a pooled prevalence of overall thrombosis in 20.7% of newly diagnosed patients with ET 1 . Moreover, a population‐based cohort study including 9429 patients with MPNs and 35 820 control participants confirmed highest rates of thromboembolic complications shortly after diagnosis, but thrombosis hazard ratios were also markedly increased at later time points compared to the control group 2 .…”
Section: Introductionmentioning
confidence: 97%